Fungi as mutualistic partners in ant-plant interactions - Mayer, Veronika E.; Voglmayr, Hermann; Blatrix, Rumsais; Orivel, Jérôme; Leroy, Céline (Frontiers in Fungal Biology, 2023)
Associations between fungi and ants living in mutualistic relationship with plants (“plant-ants”) have been known for a long time. However, only in recent years has the mutualistic nature, frequency, and geographical extent of associations between tropical arboreal ants with fungi of the ascomycete order Chaetothyriales and Capnodiales (belonging to the so-called “Black Fungi”) become clear. Two groups of arboreal ants displaying different nesting strategies are associated with ascomycete fungi: carton-building ants that construct nest walls and galleries on stems, branches or below leaves which are overgrown by fungal hyphae, and plant-ants that make their nests inside living plants (myrmecophytes) in plant provided cavities (domatia) where ants cultivate fungi in small delimited “patches”. In this review we summarize the current knowledge about these unsuspected plant-ant-fungus interactions. The data suggest, that at least some of these ant-associated fungi seem to have coevolved with ants over a long period of time and have developed specific adaptations to this lifestyle.